Identification of Throat Cancer by Machine Learning : A Surey - et. al., R. Akshara, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Medical applications in Machine Learning (ML) algorithms is well-being state on analyzing the different attributes that have a high impact on getting illness. Cancer is one amoungof the human disease where researchers are still struggling for the complete cureness and it is also unpredictable. Cancer is a heterogeneous disease and its treatment varies from one type to another and can inculcate different phases. Throat cancer is a tumor that spreads throughout the voice box (larynx), tonsils, or throat (pharynx). In the initial stage, it is actively recommended to diagnose throat cancer and get proper medication. Deep Learning (DL) image processing techniques and ML techniques are used to effectively predict the throat cancer specifically for the supervised learning classification algorithms. This paper reviewed theML and DLbased researchactivities undertaken to classify cancer of the throat cancer.